Analysis of the Effectiveness of the Family Hope Program (PKH) on Poverty Reduction in the Perspective of Islamic Economics - Sri wahyuni; Muhammad Syahrullah Langguta; Idham Khalid (IECON: International Economics and Business Conference, 2024)
This qualitative research aims to evaluate the effectiveness of the Family Hope Program (Program Keluarga Harapan/PKH) in addressing poverty in Lembo Raya District and to analyze its implementation from the perspective of Islamic economics. The study involves four informants: one program assistant from Lembo Raya District and three beneficiaries of the program. The study measures effectiveness using Ni Wayan Budiani’s effectiveness theory and employs Maqashid Syariah theory to provide an Islamic economic perspective. The findings indicate that the Family Hope Program is effective in achieving its goals of reducing poverty, supporting the economy of poor households, and enhancing human resource quality in Lembo Raya District. However, the study also identifies areas for improvement. Specifically, the program could benefit from enhanced evaluation mechanisms and the inclusion of spiritual guidance or basic religious education for both program assistants and beneficiaries. This would align the program more closely with Islamic economic principles, which emphasize holistic well-being, including spiritual and material aspects. The research highlights the importance of integrating economic and spiritual support in poverty alleviation programs to ensure sustainable outcomes. Future studies could explore broader perspectives, such as the impact of community involvement and long-term benefits, to strengthen the program’s effectiveness.